Utilization of spirillum volutans for monitoring the toxicity of effluents of a cellulose and paper industry - Lacava, Pedro Magalhães [UNESP]; Ortolono, Marcos Rogério [UNESP] (My University, 1997)
The motility of Spirillum volutans was used for monitoring the toxicity of effluents of a cellulose and paper industry Results indicated that there was no correlation between organic content and the toxic effects of the residues in the effluents. The effluents from the chlorination step and from the sludge ponds presented the highest toxicity. On the other hand, the final effluent from the biological treatment basin had no toxic agent. This bioassay showed to be a simple and reliable technique that can be used for adequately monitoring the toxicity of effluents.
Keywords: Cellulose; Paper; Spirillum volutans; Toxicity